PtCo-based composite catalyst as well as preparation method and application thereof
By using a supported PtCo-based composite catalyst in fuel cells, combining the composite of platinum-cobalt-based metal particles with non-stoichiometric transition metal oxides and mesoporous carbon support, the existing platinum-cobalt alloy catalysts are solved inadequate durability and activity. The problem of this is to achieve a more efficient and stable oxygen reduction reaction.
Patent Information
- Application Number
- CN202411518454.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-14
AI Technical Summary
The durability of the existing platinum-cobalt alloy catalysts is insufficient, and their activity needs to be further improved, and the stability of the alloy catalyst is easily lost under the conditions of fuel cells.
The supported PtCo-based composite catalyst is used, which consists of a composite of platinum-cobalt-based metal particles and a non-stoichiometric transition metal oxide HxMO3 as the support, and mesoporous carbon as the support, and modify the electron state of the platinum-cobalt surface and utilize HxMO3 as the support. Proton embedding function improves catalytic activity and stability.
It improves the activity and stability of the catalyst, enhances the efficiency of the oxygen reduction reaction, extends the service life of the catalyst, and reduces the dissolution of non-precious metals.
Smart Images

Figure CN119447338A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the technical field of fuel cell electrocatalysis, and particularly to a PtCo-based composite catalyst, a preparation method thereof, and an application thereof. Background Art
[0002] As a new form of productive force, hydrogen energy has gradually become an important direction for the high-quality development of China's energy economy. Hydrogen fuel cells are an efficient and environmentally friendly hydrogen-electric conversion technology and play an important role in accelerating the development of hydrogen energy application technologies. Among them, the cathode catalyst, as one of the core components of hydrogen fuel cells, its research and optimization are of great significance for improving the performance of fuel cells and reducing costs. Through research in recent years, in addition to the commonly used Pt / C catalyst, some alloy catalysts such as PtCo and PtNi have been proven to be able to improve fuel cell performance and reduce costs to a certain extent. However, its binding energy with O still does not reach the limit value of the activity volcano plot, and there is still room for further performance improvement. At the same time, due to the instability of non-precious metals, they are prone to loss under fuel cell operating conditions. Therefore, the durability of alloy catalysts is a bottleneck that urgently needs to be broken through.
[0003] In related technologies, CN 101176844A proposed a platinum-based composite catalyst for use as a cathode catalyst in direct methanol fuel cells, and its basic structural formula is Pt-H x WO3, 0 < x ≤ 1; the preparation method is: electro-depositing on a carbonaceous material at a constant potential in a mixed sol of H2SO4, H2PtCl6, and Na2WO4 at a certain concentration. This catalyst has the following defects: the main active metal component of the catalyst is Pt, and the oxygen reduction reaction activity is relatively low; the interaction between metal Pt and H x WO3 is weak, and the stability is poor; synthesized by electro-deposition, the size of Pt particles is not easy to control and there are difficulties in mass production and scale-up; when electro-depositing on carbonaceous materials such as carbon nanotubes and activated carbon, adhesives need to be used, which affects the activity and is not easy to prepare. CN 101362093 A proposed a fuel cell carbon-supported platinum composite catalyst and a preparation method thereof. This catalyst adds a co-catalytic component, hydrogen tungsten bronze or hydrogen molybdenum bronze, on the basis of a general carbon-supported platinum catalyst. The method for preparing this catalyst is to add tungstate or molybdate to a platinum compound solution at a suitable temperature and acidity and carry out a chemical reduction reaction in the presence of a reducing agent to obtain it. This catalyst has the following defects: the main active metal component (except for the co-catalytic component) of the catalyst is Pt and does not contain other metals, and the activity is relatively low; the active metal is single, making the interaction between the co-catalytic component and the main catalytic component weak, and the stability is poor; the carrier does not contain pores with a specific structure, the oxygen transmission is blocked, and the active metal Pt is easily poisoned by the ionomer; in addition, the synthesis method requires the addition of a complexing agent that is not easy to completely remove, thus affecting the catalytic activity. Summary of the Invention
[0004] In order to solve the problem that the durability of platinum-cobalt alloy catalyst is insufficient and the activity needs to be further improved, one object of the present application is to provide a PtCo-based composite catalyst, which is a supported catalyst, and the supported material is platinum-cobalt-based metal particles and non-stoichiometric transition metal oxide H x The composite of MO3 (M = W or / and Mo), the carrier is a mesoporous carbon carrier. Among them, the non-stoichiometric transition metal oxide H x There is a contact interface between MO3 and PtCo-based metal particles. On the one hand, MO3 can modify the electronic state of the PtCo surface to produce a synergistic catalytic effect with PtCo and improve the catalytic activity of PtCo. On the other hand, due to the H x MO3 has the function of proton insertion and extraction, which can provide protons in the oxygen reduction reaction, thus facilitating the reduction of oxygen on the catalyst surface. In addition, some platinum-cobalt-based metal particles are supported in the mesoporous structure of mesoporous carbon. These particles can avoid poisoning by sulfonic acid groups to obtain high-quality activity. At the same time, due to the confinement effect within the pores, the stability of the catalyst will be improved.
[0005] Another object of the present application is to provide a method for preparing a PtCo-based composite catalyst.
[0006] Another object of the present application is to provide an electrode.
[0007] Another object of the present application is to provide a fuel cell.
[0008] To achieve the above object, the first aspect of the present application provides a PtCo-based composite catalyst, including a carrier and a support, wherein the carrier includes mesoporous carbon, and the support includes platinum-cobalt-based metal particles and a chemical formula of H x MO3 compound, wherein M includes W and / or Mo, 0<x≤2; the platinum-cobalt-based metal particles and the chemical formula H x The compound of MO3 has a contact interface; the platinum-cobalt-based metal particles include a first part of the platinum-cobalt-based metal particles and a second part of the platinum-cobalt-based metal particles, and the platinum-cobalt-based metal particles in the first part are supported in the mesoporous structure of the mesoporous carbon.
[0009] In some embodiments, the support is a platinum-cobalt-based metal particle and a chemical formula of H x Compounds of MO3.
[0010] In some embodiments, the mass ratio of the platinum-cobalt-based metal particles in the first portion to the platinum-cobalt-based metal particles in the second portion is 1:(1-3).
[0011] In some embodiments, the second portion of the platinum-cobalt-based metal particles and at least a portion of the chemical formula H xThe MO3 compounds are all supported on the outer surface of the carrier.
[0012] In some embodiments, the second portion of the platinum-cobalt-based metal particles and the chemical formula H x The compounds of MO3 are evenly distributed.
[0013] In other embodiments, the chemical formula is H x A portion of the MO3 compound is supported on the outer surface of the carrier, and another portion is coated on the outer surface of at least a portion of the second portion of the platinum-cobalt-based metal particles.
[0014] In some further embodiments, the second portion of the platinum-cobalt-based metal particles and all of the chemical formula H x The MO3 compounds are all supported on the outer surface of the carrier.
[0015] In yet other embodiments, at least a portion of the chemical formula is H x The MO3 compound coats at least a portion of the first portion of the platinum-cobalt based metal particles.
[0016] In some embodiments, the mass ratio of platinum in the platinum-cobalt-based metal particles to the carrier is 1:(0.6-1.5).
[0017] In some embodiments, in the platinum-cobalt-based metal particles, the molar ratio of platinum to cobalt is 1:(0.1-0.8).
[0018] In some embodiments, the platinum in the platinum-cobalt-based metal particles and the chemical formula H x The molar ratio of the compound of MO3 is 1:(0.01-0.1).
[0019] In some embodiments, the average particle size of the platinum-cobalt-based metal particles is 2-6 nm.
[0020] In some embodiments, the chemical formula is H x MO3 compounds are non-chemical transition metal oxides with electrical conductivity.
[0021] In some embodiments, when M includes W, 0<x≤1.
[0022] In other embodiments, when M includes Mo, 0<x≤2.
[0023] Preferably, the chemical formula is H x The compound of MO3 is hydrogen molybdenum bronze and / or blue tungsten bronze.
[0024] In some embodiments, the chemical formula is H xMO3 compounds are amorphous porous substances.
[0025] In some embodiments, the chemical formula is H x The particle size of MO3 compounds ranges from 0.05 to 1 μm.
[0026] In some embodiments, the mesoporous carbon has a mesopore diameter of 2-50 nm.
[0027] In some embodiments, in the mesoporous carbon, the volume of mesopores with a pore diameter of 2-50 nm accounts for more than 60% of the total pore volume.
[0028] In some embodiments, in the mesoporous carbon, the volume of mesopores with a pore diameter of 2-10 nm accounts for more than 40% of the total pore volume.
[0029] In some embodiments, the first portion of the platinum-cobalt-based metal particles are supported in primary pores having a mesopore diameter of 2-10 nm.
[0030] In some embodiments, the platinum-cobalt-based metal particles further include a doping metal, and the doping metal includes at least one of Cr, La, Sm, Pb, In, Mo, Ti, Mn, Bi, Rh, Ga, and Y.
[0031] Preferably, the doping metal is at least one of Ga, Y, Pb and Sm.
[0032] In some embodiments, in the platinum-cobalt-based metal particles, the molar ratio of platinum to the doping metal is 1:(0.05-0.5).
[0033] The second aspect of the present application provides a method for preparing a PtCo-based composite catalyst, comprising:
[0034] The carbon powder is first calcined in an active gas atmosphere to obtain mesoporous carbon;
[0035] A metal salt and mesoporous carbon are first mixed in a dispersant, and then a first reducing agent is added to perform a first reduction reaction, followed by first drying and first calcination to obtain a first mixture; the metal salt comprises a platinum salt, a cobalt salt, or the metal salt comprises a platinum salt, a cobalt salt and a doped metal salt;
[0036] acid-washing, filtering and second drying the first mixture to obtain a second mixture;
[0037] The precursor of M is mixed with the second mixture for a second time, and then a second reducing agent is added to perform a second reduction reaction, followed by a third drying to obtain the PtCo-based composite catalyst powder.
[0038] In some embodiments, the reactive gas includes at least one of carbon dioxide, air, and water vapor.
[0039] In some embodiments, the temperature of the first calcination is 200-600° C., and the time of the first calcination is 1-5 hours.
[0040] In some embodiments, the dispersant includes at least one of water, ethanol, and isopropanol.
[0041] In some embodiments, the mass ratio of the mesoporous carbon to the dispersant is (0.02-0.05):1.
[0042] In some embodiments, the first mixing includes ultrasonic dispersion and mechanical stirring performed sequentially, and the time of the ultrasonic dispersion and the mechanical stirring are both 0.5-3 hours.
[0043] In some embodiments, the second calcination is performed in an inert gas atmosphere.
[0044] In some embodiments, the second calcination temperature is 400-600° C., and the second calcination time is 2-6 hours.
[0045] In some embodiments, the precursor of M includes at least one of ammonium tungstate, sodium tungstate, potassium tungstate, tungsten oxide, ammonium molybdate, sodium molybdate, potassium molybdate, and molybdenum oxide.
[0046] In some embodiments, the first reducing agent includes at least one of sodium borohydride solution, ascorbic acid, sodium citrate, and sodium formate.
[0047] In some embodiments, the first reduction reaction reduces metal ions in the metal salt to metal.
[0048] In some embodiments, the temperature of the first reduction reaction is 10-100° C., and the time of the first reduction reaction is 0.5-5 h.
[0049] In some embodiments, the second reducing agent includes zinc powder and at least one of hydrochloric acid, ascorbic acid, sodium citrate, and sodium formate.
[0050] In some embodiments, the second reduction reaction reduces the precursor of M to an amorphous porous H x MO3.
[0051] In some embodiments, the temperature of the second reduction reaction is 10-90° C., and the time of the second reduction reaction is 0.5-3 h.
[0052] A fourth aspect of the present application provides an electrode, comprising the PtCo-based composite catalyst described in the present application or a PtCo-based composite catalyst prepared by the preparation method of the PtCo-based composite catalyst described in the present application.
[0053] The fifth aspect of the present application proposes a fuel cell, comprising an anode, a cathode and a diaphragm, wherein the cathode is the electrode described in the present application.
[0054] In some embodiments, the fuel cell is a hydrogen fuel cell.
[0055] The PtCo-based composite catalyst described in this application can at least bring the following beneficial effects:
[0056] 1. PtCo-based composite catalyst, which is a supported catalyst, and the supported material is platinum-cobalt-based metal particles and non-stoichiometric transition metal oxide H x The composite of MO3 (M = W or / and Mo), the carrier is a mesoporous carbon carrier. Among them, the non-stoichiometric transition metal oxide H x There is a contact interface between MO3 and PtCo-based metal particles. On the one hand, MO3 can modify the electronic state of the PtCo surface to produce a synergistic catalytic effect with PtCo and improve the catalytic activity of PtCo. On the other hand, due to the H x MO3 has the function of proton insertion and extraction, which can provide protons in the oxygen reduction reaction, thus facilitating the reduction of oxygen on the catalyst surface. In addition, some platinum-cobalt-based metal particles are supported in the mesoporous structure of mesoporous carbon. These particles can avoid poisoning by sulfonic acid groups to obtain high-quality activity. At the same time, due to the confinement effect within the pores, the stability of the catalyst will be improved.
[0057] 2. The doping metal in the PtCo-based metal particles can, on the one hand, increase the vacancy formation energy on the catalyst surface and reduce the dissolution of non-precious metals; on the other hand, it can enhance the bonding between the active metals Pt and Co and H x MO3 (M=W or / and Mo) binding force, thereby enhancing H x MO3 (M=W or / and Mo) promotes the catalytic reaction and improves the stability of the complex structure.
[0058] 3. A portion of the PtCo-based metal particles are supported on the outer surface of the carbon support, thereby directly exposing more active sites to achieve high performance at high current density while reducing losses associated with mass transport.
[0059] 4. Appropriate amount of H x MO3 (M=W or / and Mo) is supported on the outer surface of the carrier. x MO3 is an amorphous porous substance that can provide a channel for oxygen transmission, enhance mass transfer and promote oxygen reduction.
[0060] The preparation method of the PtCo-based composite catalyst described in the present application, in addition to the beneficial effects of the PtCo-based composite catalyst of the present application, can also bring at least the following beneficial effects:
[0061] 1. The synthesis method is relatively simple and easy to scale up.
[0062] 2. The mass ratio of mesoporous carbon to dispersed solution during metal salt dispersion is 2%-5%. Within this range, metal ions of appropriate concentration are absorbed into the pores of mesoporous carbon, and part of them are loaded in the rich mesoporous structure of mesoporous carbon carrier. These particles can avoid poisoning of sulfonic acid groups to obtain high-quality activity. At the same time, due to the confinement effect in the pores, the stability of the catalyst will be improved. Another part of the PtCo-based metal particles are loaded on the outer surface of the mesoporous carbon, thereby directly exposing more active sites in order to achieve high performance at high current density.
[0063] 3. The mixed dispersion of metal salt and mesoporous carbon in the dispersant is carried out by combining ultrasound and mechanical stirring. This is because when the mass ratio of mesoporous carbon to dispersed solution is 2%-5%, the mass of dispersed solution is less and the dispersed slurry is thicker. Ultrasound can make the metal precursor solution easier to move in the nanopores, which is helpful for dispersion.
[0064] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.
[0066] in:
[0067] Figure 1 The present invention is a flow chart of a method for preparing a PtCo-based composite catalyst according to an exemplary embodiment of the present invention.
[0068] Figure 2 These are the LSV curves of the commercial platinum-carbon catalyst of Example 1, Comparative Example 7, and the commercial platinum-cobalt catalyst of Comparative Example 8.
[0069] Figure 3 Durability decay curves of commercial platinum-carbon catalysts of Example 1, Comparative Example 7, and commercial platinum-cobalt catalysts of Comparative Example 8. DETAILED DESCRIPTION
[0070] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0071] In this application, the disclosure of a numerical range includes the disclosure of all values within the entire range and further sub-ranges, including the endpoints and sub-ranges given for these ranges.
[0072] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are raw materials and equipment that can be obtained through commercial channels or prepared by known methods; the methods involved, unless otherwise specified, are conventional methods.
[0073] <PtCo-based composite catalyst>
[0074] The PtCo-based composite catalyst of the embodiments of this application includes a carrier and a load. The carrier includes mesoporous carbon, and the load includes platinum-cobalt-based metal particles and a compound with the chemical formula H x MO3, where M includes W or / and Mo, and 0 < x ≤ 2.
[0075] In some embodiments, the platinum-cobalt-based metal particles include a first part of the platinum-cobalt-based metal particles and a second part of the platinum-cobalt-based metal particles. The first part of the platinum-cobalt-based metal particles is supported within the mesoporous structure of the mesoporous carbon. The first part of the platinum-cobalt-based metal particles supported within the mesoporous structure of the mesoporous carbon can avoid the poisoning of sulfonic acid groups to obtain high-quality activity. At the same time, due to the confinement effect within the pores, the stability of the catalyst will be improved.
[0076] In some embodiments, the second part of the platinum-cobalt-based metal particles and at least part of the compound with the chemical formula H x MO3 are both supported on the outer surface of the carrier. In the embodiments of this application, part of the platinum-cobalt-based metal particles are supported on the outer surface of the carbon carrier, thereby directly exposing more active sites to achieve high performance at high current densities while reducing the losses related to mass transport.
[0077] In some embodiments, there is a contact interface between the platinum-cobalt-based metal particles and the compound with the chemical formula H x MO3.
[0078] In the embodiments of this application, the existence of a contact interface between the platinum-cobalt-based metal particles and the compound with the chemical formula H x MO3 can be understood as the existence of a contact surface between the platinum-cobalt-based metal particles and the compound with the chemical formula H x MO3. Such a contact surface can be formed by the mixed contact of the platinum-cobalt-based metal particles and the compound with the chemical formula H x MO3, formed by the planar distribution contact of the platinum-cobalt-based metal particle layer and the compound layer with the chemical formula H x MO3, or formed by the planar distribution contact of the platinum-cobalt-based metal particle layer and the compound layer with the chemical formula H xThe compound layer of MO3 forms a contact formation with a coating relationship, etc. Specifically:
[0079] In some embodiments, the second portion of the platinum-cobalt-based metal particles and the chemical formula H x The compound of MO3 is evenly distributed. At this time, the platinum-cobalt-based metal particles supported on the outer surface of the carrier and the chemical formula H x The MO3 compound is evenly distributed on the outer surface of the carrier, and the adjacent platinum-cobalt-based metal particles are connected to the chemical formula H x MO3 compound contact.
[0080] In other embodiments, the chemical formula is H x A portion of the MO3 compound is supported on the outer surface of the carrier, and another portion is coated on the outer surface of at least part of the second portion of the platinum-cobalt-based metal particles. At this time, the contact interface includes a coating interface and a planar contact interface distributed on the outer surface of the carrier.
[0081] In some other embodiments, the second portion of the platinum-cobalt-based metal particles and all of the chemical formula H x The compounds of MO3 are all supported on the outer surface of the carrier. At this time, the platinum-cobalt-based metal particle layer and the chemical formula H x The compound layer of MO3 is distributed in a plane on the outer surface of the carrier to form a coating-like structure, and the contact surfaces of the two form a contact interface.
[0082] In yet other embodiments, at least a portion of the chemical formula is H x The compound of MO3 coats at least a portion of the first portion of the platinum-cobalt-based metal particles. Here, it refers to the compound of the chemical formula H supported on the outer surface of the carrier. x The MO3 compound covers the surface of the platinum-cobalt-based metal particles within the mesoporous structure of the mesoporous carbon, and the contact surface between the two is the contact interface.
[0083] In the embodiments of the present application, H x There is a contact interface between MO3 and PtCo-based metal particles. On the one hand, MO3 can modify the electronic state of the PtCo surface to produce a synergistic catalytic effect with PtCo and improve the catalytic activity of PtCo. On the other hand, due to the H x MO3 has the function of proton insertion and extraction, and can provide protons in the oxygen reduction reaction, thus facilitating the reduction of oxygen on the catalyst surface.
[0084] As an optional example, the support is platinum-cobalt-based metal particles and a chemical formula of H x Compounds of MO3.
[0085] It should be noted that in the embodiments of the present application, in addition to mesoporous carbon, the carrier may also include carbon materials with physical and chemical properties similar to those of mesoporous carbon, other carbon materials or other carrier materials. However, the greater the proportion of mesoporous carbon in the carrier, the better the effect; when the carrier is entirely mesoporous carbon, the effect is best.
[0086] Therefore, as a preferred example, the carrier is mesoporous carbon.
[0087] In some embodiments, the mass ratio of the platinum-cobalt-based metal particles in the first part to the platinum-cobalt-based metal particles in the second part is 1:(1-3), including but not limited to 1:1, 1:2, or 1:3. In the embodiments of the present application, the mass ratio of the platinum-cobalt-based metal particles in the first part to the platinum-cobalt-based metal particles in the second part is related to factors such as the particle size of the platinum-cobalt-based metal particles, the mesoporous pore size and distribution of the mesoporous carbon, and the mass ratio of the mesoporous carbon to the dispersant in the subsequent catalyst preparation method. The more particles of the platinum-cobalt-based metal particles whose particle size is smaller than the mesoporous pore size, the larger the mesoporous pore volume, and the larger the mass ratio of the mesoporous carbon to the dispersant within the range defined in the present application, the greater the mass ratio of the platinum-cobalt-based metal particles in the first part to the platinum-cobalt-based metal particles in the second part, that is, the more platinum-cobalt-based metal particles supported in the mesoporous structure of the mesoporous carbon, and thus the more platinum-cobalt-based metal particles can avoid the poisoning of the sulfonic acid group to obtain higher mass activity, and at the same time, due to the confinement effect in the pores, the better the effect of improving the stability of the catalyst. However, the mass ratio of the platinum-cobalt-based metal particles in the first part and the platinum-cobalt-based metal particles in the second part cannot be too small or too large. If it is too small, the content of the platinum-cobalt-based metal particles in the mesoporous carbon structure will be too small, and the effect of improving the stability of the catalyst will be weakened; if it is too large, the content of the platinum-cobalt-based metal particles on the surface of the carrier will be too small, the number of directly exposed active sites will be reduced, and the ability to achieve high performance under high current density and reduce losses related to mass transport will be weakened.
[0088] In some embodiments, the mass ratio of platinum in the platinum-cobalt-based metal particles to the carrier is 1:(0.6-1.5), including but not limited to 1:0.6, 1:0.8, 1:1, 1:3 or 1:5. The mass ratio of platinum in the platinum-cobalt-based metal particles to the carrier is within the above range, which can make the metal particles in the catalyst evenly dispersed, reduce agglomeration, and increase the number of active sites. At the same time, the cathode catalyst layer of the fuel cell will have a suitable thickness, which is conducive to gas mass transfer; if it is less than 1:0.6, the metal particle loading is too high, the loading is difficult and agglomeration may occur, the electrochemical active area is reduced, and the metal utilization rate is low; if it is greater than 1:1.5, the metal particle loading is too low, and the cathode catalyst layer of the membrane electrode in the fuel cell is too thick, which affects gas mass transfer.
[0089] In some embodiments, in the platinum-cobalt-based metal particles, the molar ratio of platinum to cobalt is 1:(0.1-0.8), including but not limited to 1:0.1, 1:0.3, 1:0.5, 1:0.7 or 1:0.8, etc.
[0090] In some embodiments, the platinum in the platinum-cobalt-based metal particles and the chemical formula H x The molar ratio of the compound of MO3 is 1:(0.01-0.1), including but not limited to 1:0.01, 1:0.03, 1:0.05, 1:0.07 or 1:0.1, etc.
[0091] In some embodiments, the average particle size of the platinum-cobalt-based metal particles is 2-6 nm, including but not limited to 2 nm, 3 nm, 4 nm, 5 nm or 6 nm.
[0092] In some embodiments, the particle size range of the platinum-cobalt-based metal particles is 2-15 nm, wherein the mass content of the platinum-cobalt-based metal particles with a particle size less than 10 nm in the platinum-cobalt-based metal particles is t%, the mass content of the platinum-cobalt-based metal particles with a particle size greater than 10 nm in the platinum-cobalt-based metal particles is r%, and the ratio of t to r is 1:(1-3), including but not limited to 1:1, 1:2, or 1:3, etc.
[0093] In some embodiments, the chemical formula is H x MO3 compounds are non-chemical transition metal oxides with electrical conductivity.
[0094] In some embodiments, when M includes W, 0<x≤1.
[0095] In other embodiments, when M includes Mo, 0<x≤2.
[0096] Preferably, the chemical formula is H x The compound of MO3 is hydrogen molybdenum bronze and / or blue tungsten bronze.
[0097] In some embodiments, the chemical formula is H x MO3 compounds are amorphous porous substances that can provide channels for oxygen transmission, enhance mass transfer and promote oxygen reduction.
[0098] In some embodiments, the chemical formula is H x The particle size range of the MO3 compound is 0.05-1 μm, including but not limited to 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm or 1 μm, etc.
[0099] In some embodiments, the mesoporous carbon has a mesopore size of 2-50 nm, and the platinum-cobalt-based metal particles of the first part are preferably supported in primary pores with a mesopore size of 2-10 nm. In the embodiments of the present application, the metal ions of appropriate concentration are absorbed into the pores of the mesoporous carbon during synthesis and the particle size distribution is controlled (see the embodiment section below) to achieve this feature.
[0100] It should be noted that the carbon carrier has pores in the range of micropores, mesopores and macropores. After treatment, the proportion of mesopores of 2-50nm will increase compared to before treatment, and it is called mesoporous carbon after reaching a certain proportion. However, there will still be pores in other ranges. Among them, 2-10nm are pores (primary pores) existing on the surface of the carbon carrier itself. The metal particles are preferably supported in this part of the pores. The sulfonic acid groups of the ionomer used in the preparation of the catalytic layer cannot enter, which can avoid poisoning. The larger pores are secondary pores formed by the accumulation of carbon crystals, and the ionomer may be able to enter and poison the metal particles.
[0101] Exemplarily, the mesopore diameter of the mesoporous carbon includes but is not limited to 2 nm, 2.5 nm, 5 nm, 8 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm, etc.
[0102] In some embodiments, in the mesoporous carbon, the volume of mesopores with a pore size of 2-50 nm accounts for more than 60% of the total pore volume, including but not limited to more than 65%, more than 70%, more than 75%, more than 80%, more than 90% or more than 95%, etc.
[0103] As a preferred example, in the mesoporous carbon, the mesopore volume with a mesopore diameter of 2-10 nm accounts for more than 40% of the total pore volume, including but not limited to more than 40%, more than 55%, more than 60%, more than 65%, more than 70% or more than 75%, etc.
[0104] In some embodiments, the platinum-cobalt-based metal particles further include a doping metal.
[0105] In some embodiments, the doping metal includes at least one of Cr, La, Sm, Pb, In, Mo, Ti, Mn, Bi, Rh, Ga, and Y.
[0106] As a preferred example, the doping metal is at least one of Ga, Y, Pb, and Sm.
[0107] In the embodiment of the present application, the doping metal doped in the PtCo-based metal particles can, on the one hand, increase the vacancy formation energy on the catalyst surface and reduce the dissolution of non-precious metals; on the other hand, it can enhance the bonding between the active metals platinum and cobalt and H x MO3 (M=W or / and Mo) binding force, thereby enhancing Hx MO3 (M=W or / and Mo) promotes the catalytic reaction and improves the stability of the complex structure.
[0108] In some embodiments, in the platinum-cobalt-based metal particles, the molar ratio of platinum to the doping metal is 1:(0.05-0.5), including but not limited to 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4 or 1:0.45, etc.
[0109] As a preferred example, the platinum-cobalt-based metal particles are a Pt3Co alloy structure doped with a doping metal.
[0110] The PtCo-based composite catalyst described in this application can at least bring the following beneficial effects:
[0111] 1. PtCo-based composite catalyst, which is a supported catalyst, and the supported material is platinum-cobalt-based metal particles and non-stoichiometric transition metal oxide H x The composite of MO3 (M = W or / and Mo), the carrier is a mesoporous carbon carrier. Among them, the non-stoichiometric transition metal oxide H x There is a contact interface between MO3 and PtCo-based metal particles. On the one hand, MO3 can modify the electronic state of the PtCo surface to produce a synergistic catalytic effect with PtCo and improve the catalytic activity of PtCo. On the other hand, due to the H x MO3 has the function of proton insertion and extraction, which can provide protons in the oxygen reduction reaction, thus facilitating the reduction of oxygen on the catalyst surface. In addition, some platinum-cobalt-based metal particles are supported in the mesoporous structure of mesoporous carbon. These particles can avoid poisoning by sulfonic acid groups to obtain high-quality activity. At the same time, due to the confinement effect within the pores, the stability of the catalyst will be improved.
[0112] 2. The doping metal in the PtCo-based metal particles can, on the one hand, increase the vacancy formation energy on the catalyst surface and reduce the dissolution of non-precious metals; on the other hand, it can enhance the bonding between the active metals Pt and Co and H x MO3 (M=W or / and Mo) binding force, thereby enhancing H x MO3 (M=W or / and Mo) promotes the catalytic reaction and improves the stability of the complex structure.
[0113] 3. A portion of the PtCo-based metal particles are supported on the outer surface of the carbon support, thereby directly exposing more active sites to achieve high performance at high current density while reducing losses associated with mass transport.
[0114] 4. Appropriate amount of H x MO3 (M=W or / and Mo) is supported on the outer surface of the carrier.x MO3 is an amorphous porous material that can provide a transmission channel for oxygen, enhance mass transfer, and promote the reduction of oxygen.
[0115] <Preparation Method of PtCo-based Composite Catalyst>
[0116] The preparation method of the PtCo-based composite catalyst according to the embodiments of the present application includes the following steps:
[0117] S101. Calcinate carbon powder in an active gas atmosphere for the first time to obtain mesoporous carbon.
[0118] In some embodiments, the active gas includes at least one of, but is not limited to, carbon dioxide, air, water vapor, etc.
[0119] In some embodiments, the temperature of the first calcination is 200 - 600 °C, including but not limited to 200 °C, 300 °C, 400 °C, 500 °C, or 600 °C, etc.
[0120] In some embodiments, the time of the first calcination is 1 - 5 h, including but not limited to 1 h, 2 h, 3 h, 4 h, or 5 h, etc.
[0121] In some embodiments, the carbon powder includes at least one of, but is not limited to, activated carbon, carbon black, etc.
[0122] S102. First mix a metal salt and mesoporous carbon in a dispersant, then add a first reducing agent to perform a first reduction reaction, and then perform first drying and first calcination to obtain a first mixture; the metal salt includes a platinum salt, a cobalt salt, or the metal salt includes a platinum salt, a cobalt salt, and a doped metal salt.
[0123] In some embodiments, the first reduction reaction reduces metal ions in the metal salt to metals.
[0124] It should be noted that the molar ratio of each metal ion in the metal salt is the same as the molar ratio of each metal in the PtCo-based composite catalyst according to the embodiments of the present application, and the mass ratio of platinum to mesoporous carbon after the reduction of the metal salt is the same as the mass ratio of platinum to the carrier in the platinum-cobalt-based catalyst in the PtCo-based composite catalyst according to the embodiments of the present application.
[0125] In some embodiments, the metal salt includes at least one of metal sulfates, metal nitrates, metal chlorides, etc.
[0126] In some embodiments, the dispersant includes at least one of, but is not limited to, water, ethanol, isopropanol, etc.
[0127] In some embodiments, the mass ratio of the mesoporous carbon to the dispersant is (0.02-0.05):1, including but not limited to 0.02:1, 0.03:1, 0.04:1 or 0.05:1, etc. When the mass ratio of mesoporous carbon to dispersant is too small, too much dispersant leads to a low concentration of metal ions, and the mesoporous carbon is limited by its pore volume. The capacity of the dispersant liquid containing metal ions that can be absorbed is limited, so that the metal particle loading in the pores of the mesoporous carbon catalyst is too low, thereby affecting the activity and durability. When the mass ratio of mesoporous carbon to dispersant is too large, that is, there is too little dispersant, the mesoporous carbon carrier will not be completely wetted and cannot be evenly dispersed in the dispersant solution.
[0128] In some embodiments, the first mixing comprises sequentially performed ultrasonic dispersion and mechanical stirring.
[0129] In some embodiments, the ultrasonic dispersion and the mechanical stirring are both performed for 0.5-3 h, including but not limited to 1 h, 1.5 h, 2 h or 3 h.
[0130] In some embodiments, the first reducing agent includes but is not limited to at least one of sodium borohydride solution, ascorbic acid, sodium citrate, sodium formate, and the like.
[0131] Exemplarily, the first reducing agent is a 2-5 wt % sodium borohydride aqueous solution, such as a 3 wt % sodium borohydride aqueous solution, a 4 wt % sodium borohydride aqueous solution, or a 5 wt % sodium borohydride aqueous solution.
[0132] In some embodiments, the temperature of the first reduction reaction is 10-100°C, including but not limited to 10°C, 25°C, 50°C, 75°C or 100°C, etc.
[0133] In some embodiments, the first reduction reaction time is 0.5-5 h, including but not limited to 0.5 h, 1.5 h, 2.5 h, 3.5 h or 4.5 h, etc.
[0134] In some embodiments, the second calcination is performed in an inert gas atmosphere.
[0135] Exemplarily, the inert gas includes, but is not limited to, at least one of argon, nitrogen, helium, and the like.
[0136] In some embodiments, the second calcination temperature is 400-600°C, including but not limited to 400°C, 450°C, 500°C, 550°C or 600°C.
[0137] In some embodiments, the second calcination time is 2-6 hours, including but not limited to 2 hours, 3 hours, 4 hours, 5 hours or 6 hours.
[0138] S103, acid-washing, filtering and second drying the first mixture to obtain a second mixture.
[0139] S104, performing a second mixing of the precursor of M and the second mixture, then adding a second reducing agent to perform a second reduction reaction, and then performing a third drying to obtain the PtCo-based composite catalyst powder.
[0140] In some embodiments, the precursor of M includes but is not limited to at least one of ammonium tungstate, sodium tungstate, potassium tungstate, tungsten oxide, ammonium molybdate, sodium molybdate, potassium molybdate, molybdenum oxide, and the like.
[0141] In some embodiments, the second reducing agent includes but is not limited to zinc powder and at least one of hydrochloric acid, ascorbic acid, sodium citrate, sodium formate, and the like.
[0142] In some embodiments, the second reduction reaction reduces the precursor of M to an amorphous porous H x MO3.
[0143] In some embodiments, the temperature of the second reduction reaction is 10-90°C, including but not limited to 10°C, 25°C, 50°C, 75°C or 90°C.
[0144] In some embodiments, the second reduction reaction time is 0.5-3 h, including but not limited to 0.5 h, 1 h, 2 h or 3 h.
[0145] The preparation method of the PtCo-based composite catalyst described in the present application, in addition to the beneficial effects of the PtCo-based composite catalyst of the present application, can also bring at least the following beneficial effects:
[0146] 1. The synthesis method is relatively simple and easy to scale up.
[0147] 2. The mass ratio of mesoporous carbon to dispersed solution during metal salt dispersion is 2%-5%. Within this range, metal ions of appropriate concentration are absorbed into the pores of mesoporous carbon, and part of them are loaded in the rich mesoporous structure of mesoporous carbon carrier. These particles can avoid poisoning of sulfonic acid groups to obtain high-quality activity. At the same time, due to the confinement effect in the pores, the stability of the catalyst will be improved. Another part of the PtCo-based metal particles are loaded on the outer surface of the mesoporous carbon, thereby directly exposing more active sites in order to achieve high performance at high current density.
[0148] 3. The mixed dispersion of metal salt and mesoporous carbon in the dispersant is carried out by combining ultrasound and mechanical stirring. This is because when the mass ratio of mesoporous carbon to dispersed solution is 2%-5%, the mass of dispersed solution is less and the dispersed slurry is thicker. Ultrasound can make the metal precursor solution easier to move in the nanopores, which is helpful for dispersion.
[0149] <Electrode>
[0150] The electrode of the embodiment of the present application includes the PtCo-based composite catalyst of the embodiment of the present application or the PtCo-based composite catalyst prepared by the preparation method of the PtCo-based composite catalyst of the embodiment of the present application.
[0151] <Fuel Cell>
[0152] The fuel cell of the embodiment of the present application includes an anode, a cathode and a diaphragm, and the cathode is the electrode of the embodiment of the present application.
[0153] In some embodiments, the fuel cell includes but is not limited to at least one of a hydrogen fuel cell, a direct methanol fuel cell, a solid oxide fuel cell, etc., preferably a hydrogen fuel cell.
[0154] Certain features of the present technology are further illustrated in the following non-limiting examples.
[0155] 1. Examples and Comparative Examples
[0156] Example 1
[0157] The preparation method of the PtCo-based composite catalyst of the present embodiment comprises the following steps:
[0158] (1) Calcine the activated carbon at 400° C. for 2 h in air to obtain a mesoporous carbon carrier in which the mesopore volume accounts for 65% of the total pore volume, wherein the pore volume of 2-10 nm accounts for 45% of the total pore volume.
[0159] (2) Chloroplatinic acid containing Pt (1.95 g, 0.01 mol), cobalt nitrate containing Co (0.24 g, 0.004 mol), gallium nitrate containing Ga (0.17 g, 0.0025 mol) and 1.56 g of the mesoporous carbon support obtained in step (1) were placed in 52 g of water, ultrasonically dispersed for 1 h and mechanically stirred for 2 h to obtain a mixture A. The mass ratio of the mesoporous carbon to water was 3%.
[0160] (3) Add 30 g of sodium borohydride solution (5 wt% sodium borohydride aqueous solution) to mixture A, stir and react at room temperature 25°C for 1 hour to reduce the metal ions (i.e., platinum ions, cobalt ions and gallium ions) in the metal salts (i.e., chloroplatinic acid, cobalt nitrate and gallium nitrate) in mixture A to metals (i.e., Pt, Co and Ga) to obtain mixture B.
[0161] (4) After drying the mixture B, calcined it at 500° C. for 3 h in a nitrogen atmosphere to obtain a mixture C.
[0162] (5) Mixture C was acid-washed in a 5 wt % sulfuric acid solution at 50° C., filtered, and dried to obtain mixture D.
[0163] (6) Tungsten oxide containing W (0.092 g, 0.0005 mol) was mixed with mixture D, 100 g of water was added, and the mixture was stirred evenly to obtain mixture E.
[0164] (7) Slowly add 15 mL of 0.1 M hydrochloric acid and 0.04 g of Zn powder to the fifth mixture and stir at room temperature at 25 °C for 0.5 h to reduce tungsten oxide to amorphous H x WO3 (0<x≤1), and then dried to obtain the PtCo-based composite catalyst (PtCoGa-H x WO3 / C). The average particle size of PtCoGa metal particles is 3.8nm, H x The particle size range of WO3 is 0.05-0.2μm.
[0165] Example 2
[0166] This embodiment is basically the same as Embodiment 1, except that:
[0167] In step (6), tungsten oxide containing W (0.092 g, 0.0005 mol) is replaced with molybdenum oxide containing Mo (0.048 g, 0.0005 mol).
[0168] In step (7), molybdenum oxide is reduced to an amorphous state H x MoO3 (0<x≤2); the PtCo-based composite catalyst obtained in this embodiment is PtCoGa-H x The average particle size of MoO3 / C. PtCoGa metal particles is 4.0nm, H x The particle size range of MoO3 is 0.05-0.35μm.
[0169] Example 3
[0170] The preparation method of the PtCo-based composite catalyst of the present embodiment comprises the following steps:
[0171] (1) Calcine the activated carbon at 200° C. for 2 h in air to obtain a mesoporous carbon carrier in which the mesopore volume accounts for 60% of the total pore volume, wherein the pore volume of 2-10 nm accounts for 40% of the total pore volume.
[0172] (2) Chloroplatinic acid containing Pt (1.95 g, 0.01 mol), cobalt nitrate containing Co (0.059 g, 0.001 mol), yttrium nitrate containing Y (0.44 g, 0.005 mol) and 1.17 g of the mesoporous carbon support obtained in step (1) were placed in 23.4 g of water, ultrasonically dispersed for 2 h and mechanically stirred for 1 h to obtain a mixture A. The mass ratio of the mesoporous carbon to water was 5%.
[0173] (3) Add 24.3 g of sodium borohydride solution (5 wt% sodium borohydride aqueous solution) to mixture A, stir and react at room temperature 25°C for 1 hour to reduce the metal ions (i.e., platinum ions, cobalt ions and yttrium ions) in the metal salts (i.e., chloroplatinic acid, cobalt nitrate and yttrium nitrate) in mixture A to metals (i.e., Pt, Co and Y) to obtain mixture B.
[0174] (4) Mixture B was dried and then calcined at 400° C. for 3 h in an argon atmosphere to obtain mixture C.
[0175] (5) Mixture C was acid-washed in a 5 wt % sulfuric acid solution at 50° C., filtered, and dried to obtain mixture D.
[0176] (6) Ammonium tungstate containing W (0.018 g, 0.0001 mol) was mixed with mixture D, 50 g of water was added, and the mixture was stirred evenly to obtain mixture E.
[0177] (7) Slowly add 0.5 g of ascorbic acid to the fifth mixture and heat at 85°C for 5 h to reduce the ammonium tungstate to an amorphous state. x WO3 (0<x≤1), and then dried to obtain the PtCo-based composite catalyst (PtCoY-H x WO3 / C). The average particle size of PtCoY metal particles is 4.1nm, H x The particle size range of WO3 is 0.05-0.3μm.
[0178] Example 4
[0179] The preparation method of the PtCo-based composite catalyst of the present embodiment comprises the following steps:
[0180] (1) Calcine the activated carbon at 600° C. in water vapor for 2 h to obtain a mesoporous carbon carrier in which the mesopore volume accounts for 70% of the total pore volume, wherein the pore volume of 2-10 nm accounts for 50% of the total pore volume.
[0181] (2) Chloroplatinic acid containing Pt (1.95 g, 0.01 mol), cobalt nitrate containing Co (0.47 g, 0.008 mol), samarium nitrate containing Sm (0.75 g, 0.005 mol) and 2.93 g of the mesoporous carbon support obtained in step (1) were placed in 146.5 g of water, ultrasonically dispersed for 0.5 h and mechanically stirred for 3 h to obtain a mixture A. The mass ratio of the mesoporous carbon to water was 2%.
[0182] (3) Add 35 g of sodium borohydride solution (5 wt% sodium borohydride aqueous solution) to mixture A, stir and react at room temperature 25°C for 2 h, reduce the metal ions (i.e., platinum ions, cobalt ions and samarium ions) in the metal salts (i.e., chloroplatinic acid, cobalt nitrate and samarium nitrate) in mixture A to metals (i.e., Pt, Co and Sm), and obtain mixture B.
[0183] (4) After drying the mixture B, it was calcined at 600° C. for 3 h in an argon atmosphere to obtain a mixture C.
[0184] (5) Mixture C was acid-washed in a 5 wt % sulfuric acid solution at 50° C., filtered, and dried to obtain mixture D.
[0185] (6) Molybdenum oxide containing Mo (0.096 g, 0.001 mol) was mixed with mixture D, 150 g of water was added, and the mixture was stirred evenly to obtain mixture E.
[0186] (7) Slowly add 30 mL of 0.1 M hydrochloric acid and 0.1 g of Zn powder to the fifth mixture and stir at room temperature at 25 °C for 1 h to reduce the molybdenum oxide to an amorphous H x MoO3 (0<x≤2), and then dried to obtain the PtCo-based composite catalyst (PtCoSm-H x MoO3 / C). The average particle size of PtCoSm metal particles is 4.5nm. x The particle size range of MoO3 is 0.05-0.35μm.
[0187] Example 5
[0188] This embodiment is basically the same as Embodiment 1, except that:
[0189] In step (2), “gallium nitrate containing Ga (0.17 g, 0.0025 mol)” is removed, i.e., the catalyst does not contain doped metal Ga;
[0190] In step (3), the metal ions (i.e., platinum ions, cobalt ions) in the metal salt (i.e., chloroplatinic acid, cobalt nitrate) in the mixture A are reduced to metals (i.e., Pt, Co).
[0191] In step (7), the PtCo-based composite catalyst obtained is PtCo-H x WO3 / C. The average particle size of PtCo metal particles is 3.4nm, H x The particle size range of WO3 is 0.05-0.2μm.
[0192] Example 6
[0193] This embodiment is basically the same as Embodiment 1, except that:
[0194] The mass ratio of mesoporous carbon to water in step (2) is 1%, that is, chloroplatinic acid containing Pt (1.95 g, 0.01 mol), cobalt nitrate containing Co (0.24 g, 0.004 mol), gallium nitrate containing Ga (0.17 g, 0.0025 mol) and 1.56 g of the mesoporous carbon carrier obtained in step (1) are put into 156 g of water.
[0195] The catalyst prepared in this example is labeled as PtCoGa-H x WO3 / C 1%. The average particle size of PtCoGa metal particles is 3.3nm, H x The particle size range of WO3 is 0.05-0.2μm.
[0196] Example 7
[0197] This embodiment is basically the same as Embodiment 1, except that:
[0198] In step (2), the dispersion is not subjected to ultrasonic treatment.
[0199] The catalyst prepared in this example is labeled as PtCoGa-H x WO3 / C without ultrasound. The average particle size of PtCoGa metal particles is 4.8nm, H x The particle size range of WO3 is 0.05-0.2μm.
[0200] Example 8
[0201] This embodiment is basically the same as Embodiment 1, except that:
[0202] The mass ratio of mesoporous carbon to water in step (2) is 5.5%, that is: chloroplatinic acid containing Pt (1.95 g, 0.01 mol), cobalt nitrate containing Co (0.24 g, 0.004 mol), gallium nitrate containing Ga (0.17 g, 0.0025 mol) and 1.56 g of the mesoporous carbon carrier obtained in step (1) are put into 28.4 g of water.
[0203] The catalyst prepared in this example is labeled as PtCoGa-H x WO3 / C 5.5%. The average particle size of PtCoGa metal particles is 5nm, H x The particle size range of WO3 is 0.05-0.25μm.
[0204] Comparative Example 1
[0205] This comparative example is basically the same as Example 1, except that:
[0206] Step (6) and step (7) are not included.
[0207] The catalyst prepared in this comparative example is PtCoGa / C. The average particle size of the PtCoGa metal particles is 3.7 nm.
[0208] Comparative Example 2
[0209] This comparative example is basically the same as Example 1, except that:
[0210] The step (1) is not included, and the mesoporous carbon is replaced by activated carbon, that is, the carrier in the catalyst is activated carbon.
[0211] The catalyst prepared in this comparative example is marked as PtCoGa-H x WO3 / C 非介孔碳 The average particle size of PtCoGa metal particles is 4.6nm. x The particle size range of WO3 is 0.05-0.2μm.
[0212] Comparative Example 3
[0213] The catalyst of this comparative example is a commercial platinum-carbon catalyst (Pt / C), wherein the carbon carrier is high specific surface carbon (non-mesoporous carbon), the Pt loading is 50 wt %, and the average particle size of the Pt metal particles is 2.8 nm.
[0214] Comparative Example 4
[0215] The catalyst of this comparative example is a commercial platinum-cobalt catalyst (PtCo / C), wherein the carbon carrier is high specific surface carbon (non-mesoporous carbon), the Pt loading is 50wt%, the Co loading is 3wt%, and the average particle size of the PtCo metal particles is 5.3nm.
[0216] 2. Performance Test
[0217] Using a rotating disk electrode, the catalysts synthesized in Examples 1-8 and Comparative Examples 1-4 were tested for electrochemical active area, ORR mass activity and Pt durability.
[0218] The electrochemical active area test method is: in a 0.1 mol / L HClO4 solution saturated with N2 as the electrolyte, the catalyst is first activated for 100 CV cycles at a scanning rate of 500 mV / s, and then the catalyst is subjected to 5 CV cycles at a scanning rate of 50 mV / s, and the potential scanning range is -0.25-0.9 V (relative to saturated calomel electrode).
[0219] The ORR performance test method is: the electrolyte is 0.1 mol / L HClO4 solution saturated with O2, and resistance compensation (95%) is performed before the test. The LSV potential scanning range is 0.9-1.5V (relative to saturated calomel electrode), the scanning speed is 5mV / s, and the working electrode speed is 1600r / min.
[0220] The durability test method is as follows: in a nitrogen-saturated state in 0.1M HClO4 at 25°C, the electrode does not rotate, and one cycle is set to run at 0.95V (vs RHE) for 3s and then at 0.6V (vs RHE) for 3s. After completing every 1000 cycles, a CV scan test (50mV / s) (0.05-1.2V (vs RHE)) is performed to obtain the ECSA value, and the target number of cycles is set to 50,000.
[0221] The above performance test results are shown in Table 1 and Figure 2-3 shown.
[0222] Table 1 Performance test results
[0223]
[0224] From Table 1 and Figure 2-3 visible:
[0225] The mass specific activity and durability of Examples 1-8 are better than those of the commercial platinum-carbon and platinum-cobalt catalysts of Comparative Examples 3-4. x WO3 / C has the best ORR activity. This is because the appropriate amount of hydrogen tungsten bronze modifies the electronic state of the PtCoGa surface, and has a synergistic catalytic effect with PtCoGa, thereby improving the catalytic activity. At the same time, due to its proton insertion and extraction function, it can provide protons in the oxygen reduction reaction, which is beneficial to the reduction of oxygen on the catalyst surface. Therefore, the catalyst activity is better than that of PtCoGa / C in Comparative Example 1. PtCoGa-H in Example 1 x WO3 / C has the best durability. This is because the third metal Ga can increase the vacancy formation energy on the surface of PtCo catalyst and reduce the dissolution of non-precious metal Co. On the other hand, Ga enhances the interaction with H xThe effect of WO3 binding force improves the stability of the composite, so it is more durable than Example 5. At the same time, in Examples 1-4, due to the use of mesoporous carbon carriers, and the mass ratio of mesoporous carbon to dispersed solution when the metal salt is dispersed (step 2) is 2% to 5%, within this range, metal ions of suitable concentration are absorbed into the pores of the mesoporous carbon, and a part of them are loaded in the mesoporous structure rich in carbon carriers. This part of the particles can avoid the poisoning of the sulfonic acid group to obtain high-quality activity, and at the same time, due to the confinement effect in the pores, the stability of the catalyst will be improved, so Example 1 is better than Comparative Example 2 in activity and durability. Another part of the PtCo-based metal particles are loaded on the outer surface of the mesoporous carbon, thereby directly exposing more active sites, in order to achieve high performance at high current density. When the mass ratio of mesoporous carbon to dispersed solution is too small (Example 6 1%), too much dispersed solution leads to a low concentration of metal ions, and the mesoporous carbon is limited by the limited liquid capacity that can be absorbed by its pore volume, so that the metal particle loading in the mesoporous carbon catalyst pore is too low, thereby affecting activity and durability. When the mass ratio of mesoporous carbon to the dispersion solution is too large, that is, the dispersion solution is too little, the carbon carrier will not be completely wetted and cannot be evenly dispersed in the solution, resulting in a larger average particle size of the final catalyst metal, and reduced activity and durability (Example 85.5%). In the synthesis step (2), the dispersion is carried out by combining ultrasound and mechanical stirring. This is because when the mass ratio of mesoporous carbon to the dispersion solution is 2% to 5%, the mass of the dispersion solution is less and the dispersion slurry is thicker, which makes it easier for the metal precursor solution to move in the nanopores and helps dispersion. Therefore, when Example 7 is dispersed without ultrasonic treatment, the dispersibility of the metal particles is reduced, affecting the activity and durability.
[0226] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0227] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0228] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A PtCo-based composite catalyst, characterized in that: The invention comprises a carrier and a support, wherein the carrier comprises mesoporous carbon, and the support comprises platinum-cobalt-based metal particles and a chemical formula of H x MO3 compound, wherein M includes W and / or Mo, 0<x≤2; the platinum-cobalt-based metal particles and the chemical formula H x The compound of MO3 has a contact interface; the platinum-cobalt-based metal particles include a first part of the platinum-cobalt-based metal particles and a second part of the platinum-cobalt-based metal particles, and the platinum-cobalt-based metal particles in the first part are supported in the mesoporous structure of the mesoporous carbon.
2. The PtCo-based composite catalyst according to claim 1, characterized in that The support is platinum-cobalt-based metal particles and a chemical formula of H x MO3 compound; and / or, The mass ratio of the platinum-cobalt-based metal particles of the first part to the platinum-cobalt-based metal particles of the second part is 1:(1-3).
3. The PtCo-based composite catalyst according to claim 1, characterized in that: The second portion of the platinum-cobalt-based metal particles and at least a portion of the chemical formula H x The MO3 compounds are all supported on the outer surface of the carrier.
4. The PtCo-based composite catalyst according to claim 3, characterized in that: The platinum-cobalt-based metal particles in the second part are x The MO3 compound is evenly distributed; or, The chemical formula is H x A portion of the MO3 compound is supported on the outer surface of the carrier, and another portion is coated on the outer surface of at least a portion of the second portion of the platinum-cobalt-based metal particles; or, The second part of the platinum-cobalt-based metal particles and the entire chemical formula H x The MO3 compounds are all supported on the outer surface of the carrier; and / or, At least part of the chemical formula is H x The MO3 compound coats at least a portion of the first portion of the platinum-cobalt based metal particles.
5. The PtCo-based composite catalyst according to claim 1, characterized in that: The mass ratio of platinum in the platinum-cobalt-based metal particles to the carrier is 1:(0.6-1.5); and / or, In the platinum-cobalt-based metal particles, the molar ratio of platinum to cobalt is 1:(0.1-0.8); and / or, The platinum in the platinum-cobalt-based metal particles and the chemical formula H x The molar ratio of the compound of MO3 is 1:(0.01-0.1); and / or, The average particle size of the platinum-cobalt-based metal particles is 2-6 nm; and / or, The chemical formula is H x The compound of MO3 is a non-chemical transition metal oxide having electrical conductivity; and / or, When M includes W, 0<x≤1; and / or, When M includes Mo, 0<x≤2; and / or, The chemical formula is H x The compound of MO3 is hydrogen molybdenum bronze and / or blue tungsten bronze; and / or, The chemical formula is H x The compound of MO3 is an amorphous porous substance; and / or, The chemical formula is H x The particle size of the MO3 compound is in the range of 0.05-1 μm; and / or, The mesoporous carbon has a mesopore diameter of 2-50 nm; and / or, In the mesoporous carbon, the pore volume of mesopores with a pore diameter of 2-50 nm accounts for more than 60% of the total pore volume; and / or, In the mesoporous carbon, the volume of mesopores with a pore diameter of 2-10 nm accounts for more than 40% of the total pore volume; and / or, The platinum-cobalt-based metal particles of the first portion are supported in primary pores with a mesopore diameter of 2-10 nm.
6. The PtCo-based composite catalyst according to any one of claims 1 to 5, characterized in that: The platinum-cobalt-based metal particles further include a doping metal, and the doping metal includes at least one of Cr, La, Sm, Pb, In, Mo, Ti, Mn, Bi, Rh, Ga, and Y; Preferably, the doping metal is at least one of Ga, Y, Pb, and Sm; Preferably, in the platinum-cobalt-based metal particles, the molar ratio of platinum to the doping metal is 1:(0.05-0.5).
7. A method for preparing a PtCo-based composite catalyst according to any one of claims 1 to 6, characterized in that: include: The carbon powder is first calcined in an active gas atmosphere to obtain mesoporous carbon; A metal salt and mesoporous carbon are first mixed in a dispersant, and then a first reducing agent is added to perform a first reduction reaction, followed by first drying and first calcination to obtain a first mixture; the metal salt comprises a platinum salt, a cobalt salt, or the metal salt comprises a platinum salt, a cobalt salt and a doped metal salt; acid-washing, filtering and second drying the first mixture to obtain a second mixture; The precursor of M is mixed with the second mixture for a second time, and then a second reducing agent is added to perform a second reduction reaction, followed by a third drying to obtain the PtCo-based composite catalyst powder.
8. The preparation method according to claim 7, characterized in that: The active gas includes at least one of carbon dioxide, air and water vapor; and / or, The temperature of the first calcination is 200-600° C., and the time of the first calcination is 1-5 hours; and / or, The dispersant comprises at least one of water, ethanol and isopropanol; and / or, The mass ratio of the mesoporous carbon to the dispersant is (0.02-0.05):1; and / or, The first mixing includes ultrasonic dispersion and mechanical stirring performed sequentially, and the time of the ultrasonic dispersion and the mechanical stirring are both 0.5-3h; and / or, The second calcination is carried out in an inert gas atmosphere; and / or, The temperature of the second calcination is 400-600° C., and the time of the second calcination is 2-6 hours; and / or, The precursor of M includes at least one of ammonium tungstate, sodium tungstate, potassium tungstate, tungsten oxide, ammonium molybdate, sodium molybdate, potassium molybdate, and molybdenum oxide; and / or, The first reducing agent comprises at least one of sodium borohydride solution, ascorbic acid, sodium citrate, and sodium formate; and / or, The first reduction reaction reduces the metal ions in the metal salt to metal; and / or, The temperature of the first reduction reaction is 10-100° C., and the time of the first reduction reaction is 0.5-5 h; and / or, The second reducing agent comprises zinc powder and at least one of hydrochloric acid, ascorbic acid, sodium citrate and sodium formate; and / or, The second reduction reaction reduces the precursor of M to an amorphous porous H x MO3, and / or, The temperature of the second reduction reaction is 10-90° C., and the time of the second reduction reaction is 0.5-3 h.
9. An electrode, characterized in that: The invention comprises a PtCo-based composite catalyst as claimed in any one of claims 1 to 5 or a PtCo-based composite catalyst prepared by the preparation method as claimed in any one of claims 6 to 8.
10. A fuel cell comprising an anode, a cathode and a diaphragm, characterized in that: The cathode is the electrode as claimed in claim 9; Preferably, the fuel cell is a hydrogen fuel cell.
Citation Information
Patent Citations
Direct methanol fuel cell anode catalyzer as well as preparation method and application thereof
CN101176844A
Carbon supported platinum composite catalyst of fuel cell and preparation method thereof
CN101362093A
Cited By
Nano composite material based on porous carrier as well as preparation method and application of nano composite material
CN120109212A
Nanocomposite materials based on porous carriers and their preparation methods and applications
CN120109212B